Designing an All-Inclusive Democracy
XV, 187 p.
Keywords: Democracy is for everybody, not just a majority. This book describes the voting procedures by which majority rule may be replaced by a more consensual system of governance. In a word, such an inclusive polity can be achieved by asking the voters or, more usually, their representatives in councils and parliaments, to state their preferences, so to facilitate the identification of that option which gains the highest average preference score. The first part of the book describes three different voting procedures, the Modified Borda Count, the Quota Borda System and the Matrix Vote, and gives a number of hypothetical examples, all clearly depicted in tables. In the second part, the voting mechanisms are discussed against the background of the theory of voting, social choice theory, human rights and mediation practice. The book includes a foreword by Sir Michael Dummett and contributions by Elizabeth Meehan, Hannu Nurmi and Maurice Salles, among others.